APPLICATION OF REINFORCED EARTH IN ROADS SUBSTRUCTURE - Zafirovski Zlatko; Ognjenovic Slobodan; Gacevski Vasko; Velichkovski Ivo; Joncheski Viktor (UNIVERSITY OF MONTENEGRO FACULTY OF CIVIL ENGINEERING, 2020)
In the process of planning, i.e. of designing of the roads, it is very important to find an optimal solution. This goal most often entails many challenges and diverges from the firstly envisaged idea, but it is of extreme importance to select the best technical solution. The application of a reinforced earth construction contributes to reduction of the overall quantity of concrete works and reinforcement, necessary to construct the end pillars and their foundations. The reduction of earthworks, mainly the quantity of the excavation for the foundations and their backfilling. Besides the cost-effectiveness of the construction, the building speed is an advantage that cannot be neglected, which, in any case, implies reduction of the work force costs anyway.
Keywords: Road substructure, reinforced earth, panels, RC structure